Setting an International Research Agenda for Fear of Cancer Recurrence: An Online Delphi Consensus Study - Shaw, Joanne; Kamphuis, Helen; Sharpe, Louise; Lebel, Sophie; Smith, Allan Ben; Hulbert-Williams, Nicholas; Dhillon, Haryana Mary; Butow, Phyllis (Frontiers in Psychology, 2021)
Background Fear of cancer recurrence (FCR) is common amongst cancer survivors. There is rapidly growing research interest in FCR but a need to prioritize research to address the most pressing clinical issues and reduce duplication and fragmentation of effort. This study aimed to establish international consensus among clinical and academic FCR experts regarding priorities for FCR research. Methods Members of the International Psycho-oncology Society (IPOS) Fear of Cancer Recurrence Special Interest Group (FORwards) were invited to participate in an online Delphi study. Research domains identified in Round 1 were presented and discussed at a focus group (Round 2) to consolidate the domains and items prior to presentation in further survey rounds (Round 3) aimed at gaining consensus on research priorities of international significance. Results Thirty four research items were identified in Round 1 and 33 of the items were consolidated into six overarching themes through a focus group discussion with FCR experts. The 33 research items were presented in subsequent rounds of the delphi technique. Twenty one participants contributed to delphi round 1, 16 in round 2, and 25 and 29 participants for subsequent delphi rounds. Consensus was reached for 27 items in round 3.1. A further four research items were identified by panelists and included in round 3.2. After round 3.2, 35 individual research items were ratified by the panelists. Given the high levels of consensus and stability between rounds, no further rounds were conducted. Overall intervention research was considered the most important focus for FCR research. Panelists identified models of care that facilitate greater access to FCR treatment and evaluation of the effectiveness of FCR interventions in real world settings as the two research items of highest priority. Defining the mechanisms of action and active components across FCR/P interventions was the third highest priority identified. Conclusion The findings of this study outline a research agenda for international FCR research. Intervention research to identify models of care that increase access to treatment are based on a flexible approach based on symptom severity and can be delivered within routine clinical care were identified as research areas to prioritize. Greater understanding of the active components and mechanisms of action of existing FCR interventions will facilitate increased tailoring of interventions to meet patient need.